Řízení rizik - Hanko, Libor (Vysoké učení technické v Brně. Fakulta stavební, 2017)
Předmětem této bakalářské práce, bylo vypracování řízení rizik pro firmu z oboru stavebnictví. Teoretická část je zaměřená na obecné údaje o stavebnictví, marketingu, rozdělení rizik a také o možnostech řízení rizik. V praktické části jsou využité poznatky z teoretické části, pro určení marketingu a následné řízení rizik ve firmě.

The subject of this bachelor thesis was the development of risk management in the field of construction. The theoretical part is focused on general data on construction, marketing, risk distribution as well as on risk management options. In the practical part is used the knowledge from the theoretical part, for the determination of marketing and subsequent/followed by risk management in the company.
Risk Management
Keywords: Riziko; řízení rizik; marketingové analýzy; zdroje rizik; management rizika; identifikace rizika; analýza rizik; SWOT analýza; marketingový mix; Porterova analýza; RIPRANTM; Risk analysis; control risk management; marketing analysis; risk sources; risk management; risk identification; risk analysis; SWOT analysis; marketing mix; Porter analysis; RIPRANTM